ANALISIS KEPUASAN MAHASISWA JURUSAN MANAJEMEN DAKWAH UIN SAYYID ALI RAHMATULLAH TULUNGAGUNG TERHADAP PERKULIAHAN ONLINE - Didin Wahyudin (Ta'allum: Jurnal Pendidikan Islam, 2021)
This study aims to analyze the level of satisfaction of students of the Da'wah Management Department of UIN Sayyid Ali Rahmatullah Tulungagung with the implementation of online lectures conducted during the covid-19 pandemic. This research method uses a qualitative approach. The data were collected through questionnaires, interviews and observations on Dakwah Management students in semesters 1, 3 and 5. The collected data was then analyzed through several stages, namely the stages of data reduction, data presentation, verification and drawing conclusions. The results of this study indicate an increase in student satisfaction of the Da'wah Management Department with online lectures in the odd academic year 2021-2022. However, even though there is an increase in satisfaction with online lectures, there are still many students who want face-to-face lectures.